El recurso administrativo especial en materia de contratación a la luz de las resoluciones dictadas por el Tribunal Administrativo de Contratación Pública de la Comunidad de Madrid (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2013)
The special appeal for public procurement, has emerged from its newly established as an effective instrument of control of legality in the stages of preparation and award of public sector contracts, thereby meeting the requirements of Directives 89/665 and the current 66/2007, called appeal Directives. In this line, this special appeal allows examination of the contested acts quickly and effi- ciently, without having to go before ordinary courts. This alternative remedy has created a new body of administrative doctrine on the subject “procurement”.In this article we want to highlight the key features of the appeal and provide a review of its handling in the light of decisions rendered by the Administrative Tribunal of the Community of Madrid, since its establishment by the Plenary Agreement in May 2011, making emphasis on those aspects not specifically covered in its legal framework but constitute criteria as doctrinal body organs and resolution of contractual remedies especially Procurement Administrative Tribunal of the Community of Madrid.